Influence of positive end-expiratory pressure upregulation on the right ventricle in critical patients with acute respiratory distress syndrome: an observational cohort study - Hui Liu; Mengjie Song; Li Wang; Jianguo Xiao; Feihu Zhou (Emergency and Critical Care Medicine)
Abstract. Background. This study aimed to investigate the influence of positive end-expiratory pressure (PEEP) on the right ventricle (RV) of mechanical ventilation–assisted patients through echocardiography. Methods. Seventy-six patients assisted with mechanical ventilation were enrolled in this study. Positive end-expiratory pressure was upregulated by 4 cm H2O to treat acute respiratory distress syndrome, wherein echocardiography was performed before and after this process. Hemodynamic data were also recorded. All variables were compared before and after PEEP upregulation. The effect of PEEP was also evaluated in patients with and without decreased static lung compliance (SLC). Results. Positive end-expiratory pressure upregulation significantly affected the RV function. Remarkable differences were observed in the following: Tei index (P = 0.027), pulmonary artery pressure (P = 0.039), tricuspid annular plane systolic excursion (P = 0.014), early wave/atrial wave (P = 0.002), diaphragm excursion (P < 0.001), inferior vena cava collapsing index (P < 0.001), and SLC (P < 0.001). There were no significant changes in heart rate, respiratory rate, central venous pressure, mean arterial pressure, and base excess (P > 0.05). Furthermore, the cardiac output of the RV was not significantly affected. In patients with decreased SLC (n = 41), there were more significant changes in diaphragm excursion (P < 0.001), inferior vena cava collapse index (P = 0.025), pulmonary artery pressure (P < 0.001), and tricuspid annular plane systolic excursion (P = 0.007) than in those without decreased SLC (n = 35). Conclusion. Positive end-expiratory pressure upregulation significantly affected the RV function of critically ill patients with acute respiratory distress syndrome, especially in those with decreased SLC.